The Chicago Plan revisited': a friendly critique - Brett Fiebiger (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2014)
This paper offers a constructive critique of 'The Chicago Plan revisited' published by Jaromir Benes and Michael Kumhof (2012) as an IMF working paper. On the one hand, there are reasons to query the exact details of the proposed reform, including claims of large steady-state output gains. On the other hand, the authors deserve kudos for bringing into the foreground issues which are typically ignored or inferred otherwise by neoliberal academics and those who oversee the monetary system, including the empirical validity of the endogenous money approach and the insight that 'money' is a societal construct. The paper concludes that there is merit in revisiting '100% Reserves' as part of the theoretical rationale to expand policymaking space in debt-constrained economies.
Keywords: E50; E52; E62; 330; endogenous money; credit; banking reform; financial stability